Efficacy of Goshajinkigan for Peripheral Neurotoxicity of Oxaliplatin in Patients with Advanced or Recurrent Colorectal Cancer. (11th January 2011) - Kono, Toru; Mamiya, Noriaki; Chisato, Naoyuki; Ebisawa, Yosiaki; Yamazaki, Hirotaka; Watari, Jiro; Yamamoto, Yasuhiro; Suzuki, Shigetaka; Asama, Toshiyuki; Kamiya, Kazunori
Abstract : Peripheral neurotoxicity is the major limiting factor for oxaliplatin therapy. Goshajinkigan (GJG), a traditional Japanese herbal medicine, was recently shown to be effective in protecting against the neurotoxicity of taxanes in Japan. We retrospectively investigated the effect of GJG on peripheral neurotoxicity associated with oxaliplatin therapy. Ninety patients with metastatic colorectal cancer that received FOLFOX4 or modified FOLFOX6 therapy were assigned to receive one of the following adjuncts: oral GJG at 7.5 g day −1 (Group A, n = 11 ), intravenous supplementation of calcium gluconate and magnesium sulfate (1 g each before and after FOLFOX) (Group B, n = 14 ), combined GJG and calcium gluconate and magnesium sulfate therapies (Group C, n = 21 ), or no concomitant therapy (Group D, n = 44 ). The incidence of peripheral neurotoxicity was investigated when the cumulative dose of oxaliplatin exceeded 500 mg m −2 . When the cumulative dose of oxaliplatin exceeded 500 mg m −2, the incidence of neuropathy (all grades) in Groups A–D was 50.0%, 100%, 78.9%, and 91.7%, respectively. It was lowest in the group that received GJG alone. Concomitant administration of GJG reduced the neurotoxicity of oxaliplatin in patients that received chemotherapy for colorectal cancer.